The effect of customer experience on patient loyalty through the mediating role of patient satisfaction in inpatient services at Santa Clara Hospital Madiun - Maria Christina Ase (Universitas Nusa Cendana, 2026)
In an increasingly competitive healthcare environment, enhancing patient loyalty has become a strategic priority for hospitals seeking to ensure service sustainability and long-term patient retention. This study examines the effect of Customer Experience on Patient Loyalty, with Patient Satisfaction serving as a mediating variable, in inpatient services at Santa Clara Hospital Madiun, Indonesia. A quantitative research design was employed using a survey method involving 139 non-BPJS patients selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings indicate that Customer Experience has a positive and significant effect on Patient Satisfaction and Patient Loyalty. Patient Satisfaction also positively influences Patient Loyalty and partially mediates the relationship between Customer Experience and Patient Loyalty. The structural model demonstrates substantial explanatory power, with Customer Experience accounting for 77.3% of the variance in Patient Satisfaction, while Customer Experience and Patient Satisfaction jointly explain 78.6% of the variance in Patient Loyalty. These results suggest that delivering superior patient experiences is essential for fostering patient satisfaction and strengthening loyalty in healthcare settings. The study contributes to the healthcare service management literature by providing empirical evidence on the mechanisms through which patient experiences shape loyalty outcomes in hospital environments. The findings offer practical implications for healthcare managers seeking to improve patient retention through integrated strategies that prioritize service quality, patient-centered care, and satisfaction enhancement. Keywords: Customer Experience; Patient Satisfaction; Patient Loyalty; Inpatient Services; PLS-SEM